Antagonistic controls regulate copy number of the yeast 2 mu plasmid. - Murray, J A (1987)
The endogenous 2 mu plasmid of yeast encodes a site-specific recombinase FLP that can cause an amplification of plasmid copy number. Using strains overexpressing 2 mu plasmid proteins from chromosomal constructs to disrupt the normal balance of gene products, we show here that copy number is controlled by regulating the transcript level of FLP. Expression of FLP is negatively regulated over a 100-fold range by the joint action of the plasmid-encoded REP1 and REP2 proteins, which also have a role in plasmid partition. We also show that the product of the fourth plasmid open reading frame D increases FLP expression by relieving the repression caused by REP1 and REP2. This is the first demonstration of a function for this gene, which we call RAF. The transcription of RAF is also repressed by REP1 and REP2 acting together, but requires a higher level for complete inhibition than that required to repress FLP. Copy number is therefore negatively regulated by REP1-REP2 concentration both by direct repression of FLP and indirectly, by control of the positive element, the anti-repressor RAF. We propose that these antagonistic regulatory mechanisms amplify the signal produced by a small fall in copy number.